Usulan Strategi Optimalisasi Akun Media Sosial Dalam Upaya Meningkatkan Reach Melalui Instagram Advertising (Studi Kasus: Humingbad Clothing) - Fahri Setia; Cecep Safaatul Barkah (Jurnal Sekretaris dan Administrasi Bisnis, 2022)
The success of a company is not only seen from profits, but many other factors that influence it. This research is motivated by the level of reach that the company gets through social media, which can be seen by the company's way of digital promotion. This study aims to determine how to determine the right strategy in increasing the reach or reach on the Hummingbad Clothing Instagram account with descriptive qualitative methods, data collection is done by interview and also observation. The data obtained were processed using a number of methods of analysis of Sustainable Competitive Advantage (SCA), VRIO model analysis and TOWS analysis. Then the researcher analyzed Hummingbad Clothing's Instagram account with the Reach marketing matrix to propose a strategy to increase reach through advertising. The recommended suggestion is the use of Instagram Ads.